Development of a Salutogenesis Workshop for SPPs to Help Them, Their Athletes, and the Athlete’s Entourage Better Cope With Uncertainty During the COVID-19 Pandemic - Leisterer, Sascha; Lautenbach, Franziska; Walter, Nadja; Kronenberg, Lara; Elbe, Anne-Marie (Frontiers in Psychology, 2021)
The COVID-19 pandemic is also called a crisis of uncertainty because of so many unforeseeable events like canceled qualification competitions, loss of training facilities, and postponement of the Olympic games. Athletes and their entourage experience this uncertainty as stressful. Sport psychology practitioners (SPPs) are in a key position to support athletes in coping with these unforeseeable stressors. However, SPPs are similarly affected by the COVID-19 pandemic and simultaneously have to cope with stress. Salutogenesis, which describes how to manage stress and to stay well, provides a theoretical approach to how to cope with uncertainty. The salutogenetic approach aims at strengthening individuals’ sense of coherence (SoC) and consists of three components, namely comprehensibility, manageability, and meaningfulness. Although it is known that the SoC can be enhanced via psychological skills training, so far, this approach has not been systematically applied to the elite sport context. Athletes have been advised to see SPPs for help; thus, the question of how SPPs handle the time of uncertainty while supporting others emerges. The aim of this contribution was to outline how the salutogenetic approach can be applied to strengthening SPPs’ SoC via a single-day four-part workshop. Additionally, we applied the workshop to N = 26 volleyball coaches and evaluated the workshop’s effects on participants’ psychological aspects [i.e., the Sense of Coherence—Leipziger short version (SoC-L9), resilience (RS-13): coping with uncertainty, affective response, and stress via semantic differentials] and the workshop’s quality ratings (i.e., Quality Questionnaire for Sport Psychological Coaching, QS-17). The evaluation provides results that show a positive impact on a descriptive level of the participants’ SoC, uncertainty, affect, and stress perception; however, the results show no significant main effect of time [F(8, 10) = 1.04, p = 0.467, ηp2 = 0.454]. Workshop quality (on average, 3.60 ± 0.35 out of 4.00) and skill acquisition (on average, 3.00 ± 0.64 out of 4.00) were positively evaluated; 82.00% of the participants would use the learned tools in the future. Thus, we outline how this workshop might help strengthen SPPs’ SoC and at the same time empower them to strengthen their athletes’ SoC. Overall, we add a theoretical (i.e., salutogenesis in sports) and a practical perspective (i.e., coping techniques based on salutogenesis) on how to cope with the COVID-19 pandemic for SPPS, athletes, and their support network.